So this is ever after - Lukens, F. T. (Margaret K. McElderry Books, 2022)
Arek has managed to fulfill the prophecy and save the Kingdom of Ere from its evil ruler, but the quest is not over because until they free the princess locked in one of the towers he has to assume the crown himself; only the princess proves to be very dead, and Arek is stuck as king; then he discovers that magic requires him to find a bride before his eighteenth birthday or wither away--but none of his female companions are interested, he does not want to marry a stranger, and anyway the only person he is attracted to is Matt, aspiring wizard, best friend, and secret crush.